1992
DOI: 10.1159/000468779
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Heterogeneity in the Metabolism of Amino Acids and Ammonia

Abstract: With respect to hepatocyte heterogeneity in ammonia and amino acid metabolism, two different patterns of sublobular gene expression are distinguished: ‘gradient-type’ and ‘strict- or compartment-type’ zonation. An example for strict-type zonation is the reciprocal distribution of carbamoylphosphate synthase and glutamine synthase in the liver lobule. The mechanisms underlying the different sublobular gene expressions are not yet settled but may involve the development of hepatic architecture, innervation, bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
136
2
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 208 publications
(150 citation statements)
references
References 46 publications
10
136
2
2
Order By: Relevance
“…Therefore, the fraction of GS in normal liver that can be attributed to KCs will be less than 1%. After liver injury or cirrhosis, however, when the hepatic GS activity drops to values below 20% of control (Häussinger et al 1992), KCs and, as shown previously, transformed hepatic stellate cells (Bode et al 1998) may contribute significantly to total hepatic glutamine synthesis.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, the fraction of GS in normal liver that can be attributed to KCs will be less than 1%. After liver injury or cirrhosis, however, when the hepatic GS activity drops to values below 20% of control (Häussinger et al 1992), KCs and, as shown previously, transformed hepatic stellate cells (Bode et al 1998) may contribute significantly to total hepatic glutamine synthesis.…”
Section: Discussionsupporting
confidence: 67%
“…Liver cirrhosis in animal models and man and hepatocellular carcinoma are associated with strongly reduced GS activity, followed by hyperammonemia (2,(55)(56)(57). In cirrhosis with collaterals, down-regulation of GS in scavenger cells may be related to portocaval shunting (3,58,59). Here, it should be noted that glutaminase activity in the cirrhotic liver increases four-to fivefold to compensate for a marked reduction of the capacity for urea synthesis, thereby maintaining a life-compatible urea cycle flux (55).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic urea synthesis in periportal hepatocytes is dependent on the activity of carbamoylphosphate synthetase, the rate-controlling enzyme of the urea cycle requiring ammonia as a substrate (3). The affinity of carbamoylphosphate synthetase for ammonia is low, and adequate flux through the urea cycle requires the establishment of high ammonia concentrations in periportal hepatocytes, which is achieved through ammonia amplification by periportal glutaminase activity (1-3).…”
mentioning
confidence: 99%
“…3,4 For the detoxification of ammonia, the liver contains both ureaity of the hepatocytes along the portocentral radius of the liver lobule, has been studied extensively. 1,2 The metabolism of and glutamine-synthesizing enzyme systems that have a reciprocal distribution pattern.…”
mentioning
confidence: 99%